Does FDI mode of entry have an impact on the host country’s labor productivity?: An analysis of the EU countries - Dražen Derado; Darko Horvatin (Ekonomski Vjesnik, 2019)
Economic growth results from the interplay of labor, capital and technology. In that respect, foreign direct investment (FDI) plays an important role, as it brings not only funds, but also intangible assets (technology and know-how) which contribute to the productivity growth of the recipient country. However, empirical findings on the impact of FDI on the host country’s productivity and economic growth are not quite straightforward, as they sometimes indicate not only positive, but also modest, or even negative effects. Hence, the aim of the paper is to investigate the impact of FDI on the host country’s productivity with reference to different FDI modes of entry, as well as the level of innovativeness of the FDI recipient countries. Results of the panel data analysis with fixed effects on the sample of the EU countries cast a new light on the expected effects of FDI, since mergers and acquisitions (M&A) prove to have a stronger impact on the local economy’s productivity with countries at a higher level of innovativeness, while greenfield investments exert stronger positive effects in the case of technologically less advanced economies.